Implementasi Metode Role-Play dalam Meningkatkan Kemampuan Berbicara Bahasa Arab di Sekolah Islam - Hilwa Wafin Nur, Hilwa Wafin Nur; Syaiful Mustofa, Syaiful Mustofa; Usfiyatur Rusuly, Usfiyatur Rusuly (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research discusses the implementation of the role-play method in enhancing Arabic language speaking skills in Islamic schools in Indonesia. The role-play method is a creative activity in which participants assume fictional character roles and engage in a simulated environment or scenario. However, there are several challenges and constraints in its implementation, such as time limitations, students' limited understanding of the Arabic language, and adjustments to the learning schedule. Therefore, efforts to improve the effectiveness of this method require changes in the allocation of learning time and an approach that focuses on understanding the students' needs. The role-play method offers several advantages in an educational context, such as providing practical experiences to participants, enhancing speaking and communication skills, developing social skills, understanding different perspectives, and increasing motivation and engagement. However, this method also has some disadvantages, including participant fear and nervousness, the need for additional time in the learning process, resource limitations, and subjective assessment. Educators and students need to carefully consider the pros and cons of this method before implementing it.